INNOVATIVE APPROACHES OF ISLAMIC RELIGIOUS EDUCATION TEACHERS TO ENHANCE STUDENT LEARNING ENTHUSIASM - Reni Marlena; Rahmat Alpan Wira Cahyadi; Muslih Hidayat; Imam Hambali (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Islamic Religious Education (IRE) plays an essential role in shaping the character and morality of students. This article discusses the innovative approaches IRE teachers apply to enhance students’ enthusiasm for learning. This study aims to explore various creative methods that can be implemented in IRE teaching to motivate students to be more active and enthusiastic in participating in lessons. This research uses a qualitative descriptive approach. The descriptive study aims to provide an in-depth overview of the innovative methods employed by Islamic Religious Education teachers to increase students’ enthusiasm for learning. Data was collected through interviews, observations, and documentation. The validity of the data was ensured through triangulation techniques, which validated the gathered information. Data analysis was performed using the interactive methods of Miles and Huberman, which involve four stages: data collection, data reduction, data presentation, and conclusion.